2018
DOI: 10.2478/contagri-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Color Shade Nets Improve Vegetables Quality at Harvest and Maintain Quality During Storage

Abstract: Summary The photoselective, light-dispersive shade nets can be used as an alternative to protect crops from adverse environmental conditions such as; excessive solar radiation, heat and drought stress, wind and hail, birds, flying pests, thus improving crop’s production, yield and quality. The physiological parameters discussed in the review include: vegetable growth parameters (leaf area, leaf chlorophyll), tissue structure, fruit ripening, physiological disorders, pest and disease incidence, fruit quality pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…Specifically, the decreased carotenoid contents in 'Ballerina' and 'Canasta' are in agreement with Gerganova et al [57]. In contrast, 'Oak leaf' and 'Romaine' maintained the content of this crucial bioactive molecule unchanged, probably as a defense system to high irradiance intensity, because these pigments act as photo-selective filters [58]. The current results are not in line with the findings of Rouphael et al [59], where 'Red Oak leaf' and 'Baby Romaine' demonstrated significantly lower carotenoid concentrations when grown under lower irradiance in a controlled environment.…”
Section: Fluorescence Total Ascorbic Acid and Carotenoids Content Of Lettuce Under Excessive Irradiance And Heat Conditionssupporting
confidence: 87%
“…Specifically, the decreased carotenoid contents in 'Ballerina' and 'Canasta' are in agreement with Gerganova et al [57]. In contrast, 'Oak leaf' and 'Romaine' maintained the content of this crucial bioactive molecule unchanged, probably as a defense system to high irradiance intensity, because these pigments act as photo-selective filters [58]. The current results are not in line with the findings of Rouphael et al [59], where 'Red Oak leaf' and 'Baby Romaine' demonstrated significantly lower carotenoid concentrations when grown under lower irradiance in a controlled environment.…”
Section: Fluorescence Total Ascorbic Acid and Carotenoids Content Of Lettuce Under Excessive Irradiance And Heat Conditionssupporting
confidence: 87%
“…Immediately after harvest, the use of field shades to keep the produce cool also reduces the amount of heat load in the produce. Field shades cool produce, thus decreasing metabolic reactions in harvested produce [11]. Harvested produce should be transported from the field to storage immediately.…”
Section: Introductionmentioning
confidence: 99%
“…The photoselective screens increase the diffused radiation, normalize excessive levels of light, temperature, humidity and wind velocity [ 12 ] which allow for the greater efficiency of vegetable production in protected cultivation [ 13 ]. In addition, photoselective nets improve the quality of vegetables at harvest [ 14 ] and at the post-harvest stage [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%